Global, regional, and national burdens of endometriosis from 1990 to 2021: a trend analysis - Hailan Yan; Hailan Yan; Xiaoyan Li; Xiaoyan Li; Yi Dai; Yi Dai; Jinghua Shi; Jinghua Shi; Yushi Wu; Yushi Wu; Zhiyue Gu; Zhiyue Gu; et al. (Frontiers in Medicine)
BackgroundEndometriosis is a common, chronic, estrogen-dependent gynecological disorder that significantly affects patients’ quality of life. However, the disease burden and its trends may be undergoing significant changes, and comprehensive data on this issue are currently lacking. This study aimed to examine trends in the burden of endometriosis at the global, national, and regional levels.MethodsWe collected detailed data on incidence numbers, disability-adjusted life years (DALYs), age-standardized incidence rate (ASIR), and age-standardized DALY rate (ASDR) for the period 1990–2021 from the GBD 2021 database. We calculated the estimated annual percentage changes (EAPCs) to quantify the temporal trends in the ASIR and ASDR of endometriosis and presented the global distribution of these trends.ResultsThe global incident cases of endometriosis were 3.45 million (95% uncertainty interval [UI] = 2.44 to 4.6), and DALYs were 2.05 million (95% UI = 1.20 to 3.13). The global ASIR decreased from 1990 to 2021 (EAPC = −1.01, 95% UI = −1.06 to −0.96), while the ASDR was similar (EAPC = −0.99, 95% UI = −1.04 to −0.95). The age groups with the highest global incidence and DALYs were 20–24 and 25–29 years. The highest 2021 ASIR and ASDR were both in Niger (77.33 per 100,000 individuals, 95% UI = 52.74 to 106.78; 61.45 per 100,000 individuals, 95% UI = 34.29 to 95.47) and in Oceania (77.71 per 100,000 individuals, 95% UI = 51.23 to 100.27; 45.24 per 100,000 individuals, 95% UI = 45.24 to 71.95). In 2021, the ASIR and ASDR were highest in the low sociodemographic index (SDI) region. We also found that the EAPC was negatively correlated with ASIR in 1990 (ρ = −0.55, p < 0.001) and positively correlated with Human Development Index (HDI) in 2021 (ρ = 0.556, p < 0.001).ConclusionThe global burden of endometriosis remains substantial and has continued to rise across most countries, territories, and regions since the 1990s, underscoring the urgent need for targeted public health strategies and advancements in diagnosis and treatment to address this pervasive condition.